МАХТУМҚУЛИНИНГ БАЪЗИ ЎЗБЕКЧА ШЕЪРЛАРИ ТАРЖИМАСИДА ВАЗННИНГ АҲАМИЯТИ - Сапаева, Ф. (SCIENCE and SOCIETY, 2018)
In the article the genre structure of Maktumkuli‘s poems and their Uzbek translations are studied from the point of view of meters. His poems were translated inti Uzbek by Uzbek translators M.Shayhzoda, J.Sharipov, E.Ochilov, M.Ahmad, M.Azim, O.Safarov. Their works are considered as the object of the research. Samples of analyses were discussed in the Uzbek and Turkmen languages.
Keywords: Махтумқули; шеър; бадиий таржима; туркман тили; ўзбек тили; мазмун; маъно; аслият; вазн; туроқ; ҳижо; қофия; таржимон